2004
DOI: 10.1002/dvdy.20152
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a novel transcript down‐regulated in Dlx1/Dlx2 and up‐regulated in Pax6 mutant telencephalon

Abstract: By using a custom-made array containing cDNAs preferentially expressed in the mouse embryonic telencephalon (Porteus et al. [1992] Brain Res Mol Brain Res 12:7-22; and Alessandro Bulfone, unpublished data), we studied the gene expression profile of the Dlx1/Dlx2 -/-subpallium and Pax6 -/-pallium. We identified a transcript corresponding to Unigene Cluster Mm.94021 and rat Evf-1, which is down-regulated in the Dlx1/Dlx2 -/-subpallium and up-regulated in the Pax6 -/-pallium. Here, we report the expression patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…As has been described previously (Faedo et al, 2004), during the systematic analysis of the TESS transcripts, we found a putative noncoding RNA TESS 31.E5, an ortholog of the rat Evf-1 (AY518691) (Kohtz and Fishell, 2004). Therefore, this confirms the relevance of our approach and the importance of the isolation and characterization of the TESS cDNA library.…”
Section: Discussionsupporting
confidence: 87%
“…As has been described previously (Faedo et al, 2004), during the systematic analysis of the TESS transcripts, we found a putative noncoding RNA TESS 31.E5, an ortholog of the rat Evf-1 (AY518691) (Kohtz and Fishell, 2004). Therefore, this confirms the relevance of our approach and the importance of the isolation and characterization of the TESS cDNA library.…”
Section: Discussionsupporting
confidence: 87%
“…1a). We isolated a full-length cDNA containing ei sequences from a rat embryonic day 15.5 (E15.5) brain library, and found it to be a 3.8-kb alternatively spliced form of Evf-1, an ncRNA previously identified as a downstream target of Shh signaling in the rat embryonic forebrain (Kohtz et al 1998;Faedo et al 2004;Kohtz and Fishell 2004). We named this 3.8-kb, ei-containing alternatively spliced form of Evf-1, Evf-2.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, Pax6 has been shown to play an important role promoting neurogenesis. In vivo, loss of Pax6 results in neural progenitors having reduced neurogenic potential [24,25], whereas its over-expression in vitro pushes cells towards a neuronal fate [24][25][26]. Altogether, cxcr4, id2, pax3, and pax6 over-expression seem to be responsible for neuronal fate decision.…”
Section: Discussionmentioning
confidence: 99%